Phagocytosis and Killing of Staphylococcus aureus by Human Neutrophils - Lu, Thea (S. Karger AG, 2014)
Neutrophils are essential for host defense against Staphylococcus aureus infections. Although significant progress has been made, our understanding of neutrophil interactions with S. aureus remains incomplete. To provide a more comprehensive view of this process, we investigated phagocytosis and killing of S. aureus by human neutrophils using varied assay conditions in vitro. A greater percentage of bacteria were internalized by adherent neutrophils compared to those in suspension, and, unexpectedly, uptake of S. aureus by adherent neutrophils occurred efficiently in the absence of opsonins. An antibody specific for S. aureus promoted uptake of unopsonized bacteria in suspension, but had little or no capacity to enhance phagocytosis of S. aureus opsonized with normal human serum or by adherent neutrophils. Collectively, these results indicate that assay conditions can have a significant influence on the phagocytosis and killing of S. aureus by neutrophils. More importantly, the results suggest a vaccine approach directed to enhance opsonophagocytosis alone is not sufficient to promote increased killing of S. aureus by human neutrophils. With the emergence and reemergence of antibiotic-resistant microorganisms, establishing parameters that are optimal for studying neutrophil-S. aureus interactions will pave the way towards developing immune-directed strategies for anti-staphylococcal therapies.